Cemented carbide and tool comprising cemented carbide

By introducing specific tungsten carbide particles, TinbC compounds, and high -content cobalt binding phases in the hard alloy, optimize the particle size distribution and decentralization of each phase, solve the problem of short life of the existing hard alloy tools, and realize the tools of the tools. Long life and high abrasion resistance.

CN119365618APending Publication Date: 2025-01-24SUMITOMO ELECTRIC HARDMETAL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380046311.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-05-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The tool life of existing cemented carbides is shorter in energy-efficient processing of difficult-to-cut materials, making it difficult to meet the requirements of cost reduction and longevity.

Method used

Using a first hard phase composed of tungsten carbide particles, a second hard phase including TiNbC, TiNbN, TiNbCN and other compounds, and a cemented carbide composed of a binding phase containing more than 80% cobalt, by optimizing the particle size of each phase Distribution and dispersion improve the wear resistance, chip resistance and welding resistance of the tool.

Benefits of technology

It realizes the long life of the tool, improves the mechanical strength and welding resistance of the carbide, and extends the service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365618A_ABST
    Figure CN119365618A_ABST
Patent Text Reader

Abstract

This cemented carbide is configured from a first hard phase, a second hard phase, and a binder phase, the first hard phase being configured from tungsten carbide particles, the 10% cumulative particle diameter (D10) of the first hard phase on an area basis being 0.30-0.60 [mu] m inclusive, the 90% cumulative particle diameter (D90) of the first hard phase on an area basis being 0.90-1.40 [mu] m inclusive, and the binder phase being a mixture of the first hard phase and the second hard phase. The second hard phase contains at least one first compound selected from the group consisting of TiNbC, TiNbN, and TiNbCN, the content of the second hard phase in the cemented carbide is 0.10-0.50 vol% inclusive, the average particle diameter of the second hard phase is 0.03-0.50 [mu] m inclusive, the binder phase contains 80% by mass or more of cobalt, and the content of the binder phase is less than or equal to 1% by mass and less than or equal to 1% by mass. The content of the binding phase in the cemented carbide is 8.0 vol% or more and 16.0 vol% or less, the average particle diameter of the binding phase is 0.15 [mu] m or more and 0.45 [mu] m or less, the 95% cumulative particle diameter D95 of the binding phase on an area basis is 1.5 [mu] m or less, and the degree of dispersion of the binding phase is 0.15 or more and 0.25 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to cemented carbide and tools containing cemented carbide. Background Art

[0002] Conventionally, cemented carbide having a phase containing tungsten carbide (WC) as a main component and a bonding phase containing an iron group element as a main component has been used as a material for cutting tools (Patent Documents 1 to 5).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-024214

[0006] Patent Document 2: Japanese Patent Application Publication No. 2013-060666

[0007] Patent Document 3: International Publication No. 2018 / 180911

[0008] Patent Document 4: Japanese Patent Application Publication No. 2021-134364

[0009] Patent Document 5: Japanese Patent Application Publication No. 2016-098393 Summary of the invention

[0010] The cemented carbide disclosed in the present invention is a cemented carbide composed of a first hard phase, a second hard phase, and a bonding phase, wherein:

[0011] The first hard phase is composed of tungsten carbide particles,

[0012] The 10% cumulative grain size D10 of the first hard phase on an area basis is 0.30 μm or more and 0.60 μm or less,

[0013] The 90% cumulative grain size D90 of the first hard phase on an area basis is 0.90 μm or more and 1.40 μm or less,

[0014] The second hard phase includes at least one first compound selected from the group consisting of TiNbC, TiNbN and TiNbCN,

[0015] The content of the second hard phase in the cemented carbide is 0.10 volume % or more and 0.50 volume % or less,

[0016] The average grain size of the second hard phase is 0.03 μm or more and 0.50 μm or less.

[0017] The binding phase contains 80 mass % or more of cobalt,

[0018] The content of the binder phase in the cemented carbide is 8.0 volume % or more and 16.0 volume % or less,

[0019] The average particle size of the binder phase is 0.15 μm or more and 0.45 μm or less,

[0020] The 95% cumulative particle size D95 based on the area of ​​the bonding phase is 1.5 μm or less,

[0021] The dispersion degree of the binder phase is 0.15 or more and 0.25 or less. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a diagram showing an example of a reflected electron image of cemented carbide according to the first embodiment.

[0023] Figure 2 is based on Figure 1 The Voronoi diagram made from the reflected electron image shown. DETAILED DESCRIPTION

[0024] Problems to be solved by the present disclosure

[0025] In recent years, the demand for cost reduction has become increasingly stringent, and for example, in the energy-efficient processing of difficult-to-cut materials such as titanium alloys and stainless steel, tools with long life are also sought. Therefore, an object of the present disclosure is to provide a cemented carbide and a tool containing the cemented carbide that can achieve a long tool life when used as a tool material.

[0026] Effects of the present disclosure

[0027] When the cemented carbide of the present disclosure is used as a tool material, the tool life can be prolonged. A tool including the cemented carbide of the present disclosure can have a long tool life.

[0028] [Description of Embodiments of the Present Disclosure]

[0029] First, embodiments of the present disclosure are listed and described.

[0030] (1) The cemented carbide disclosed in the present invention is a cemented carbide composed of a first hard phase, a second hard phase, and a bonding phase, wherein:

[0031] The first hard phase is composed of tungsten carbide particles,

[0032] The 10% cumulative grain size D10 of the first hard phase on an area basis is 0.30 μm or more and 0.60 μm or less,

[0033] The 90% cumulative grain size D90 of the first hard phase on an area basis is 0.90 μm or more and 1.40 μm or less,

[0034] The second hard phase includes at least one first compound selected from the group consisting of TiNbC, TiNbN and TiNbCN,

[0035] The content of the second hard phase in the cemented carbide is 0.10 volume % or more and 0.50 volume % or less,

[0036] The average grain size of the second hard phase is 0.03 μm or more and 0.50 μm or less.

[0037] The binding phase contains 80 mass % or more of cobalt,

[0038] The content of the binder phase in the cemented carbide is 8.0 volume % or more and 16.0 volume % or less,

[0039] The average particle size of the binder phase is 0.15 μm or more and 0.45 μm or less,

[0040] The 95% cumulative particle size D95 based on the area of ​​the bonding phase is 1.5 μm or less,

[0041] The dispersion degree of the binder phase is 0.15 or more and 0.25 or less.

[0042] When the cemented carbide disclosed in the present invention is used as a tool material, it is possible to extend the life of the tool.

[0043] (2) According to (1) above, in the cemented carbide, the mass percentage of niobium relative to the total of titanium and niobium may be 3% to 20%. This allows the second hard phase to be finely dispersed in the cemented carbide, thereby improving the welding resistance of the cemented carbide.

[0044] (3) According to (1) or (2) above, the dispersion is the standard deviation of the area of ​​each Voronoi region in the Voronoi diagram obtained by Voronoi segmentation with the center of gravity of the second hard phase as the parent point,

[0045] The Voronoi diagram is obtained in the following manner: the second hard phase is extracted from a reflected electron image obtained by photographing a cross section of the cemented carbide using a scanning electron microscope, a rectangular measurement field of 24.9 μm×18.8 μm is set in the image after binarization of the reflected electron image, and in the measurement field, Voronoi segmentation is performed with the center of gravity of the extracted second hard phase as the mother point, and the Voronoi areas of all the mother points are calculated.

[0046] (4) The present disclosure is a tool comprising the cemented carbide according to any one of (1) to (3). The tool of the present disclosure can have a long tool life.

[0047] [Details of the embodiments of the present disclosure]

[0048] In the present disclosure, expressions in the form of “A to B” refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit recorded in A and only the unit is recorded in B, the unit of A is the same as the unit of B.

[0049] In the present disclosure, when a compound is represented by a chemical formula, when there is no particular limitation on the atomic ratio, all conventionally known atomic ratios are included, and it is not necessarily limited to the stoichiometric range. For example, when described as "TiNbC", the ratio of the number of atoms constituting TiNbC includes all conventionally known atomic ratios.

[0050] In the present disclosure, when pressure is indicated, unless otherwise specified, it means pressure based on atmospheric pressure.

[0051] The following is a description of the specific examples of the cemented carbide disclosed herein and the tools containing the cemented carbide with reference to the accompanying drawings. In the accompanying drawings disclosed herein, the same reference numerals represent the same parts or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, depth, etc. are appropriately changed for the clarity and simplification of the accompanying drawings, and do not necessarily represent the actual dimensional relationships.

[0052] [Implementation method 1: cemented carbide]

[0053] A cemented carbide according to one embodiment of the present disclosure (hereinafter also referred to as “embodiment 1”) is a cemented carbide composed of a first hard phase, a second hard phase, and a binder phase, wherein:

[0054] The first hard phase is composed of tungsten carbide particles,

[0055] The 10% cumulative grain size D10 of the first hard phase on an area basis is 0.30 μm or more and 0.60 μm or less,

[0056] The 90% cumulative grain size D90 of the first hard phase on an area basis is 0.90 μm or more and 1.40 μm or less,

[0057] The second hard phase includes at least one first compound selected from the group consisting of TiNbC, TiNbN and TiNbCN,

[0058] The content of the second hard phase in the cemented carbide is 0.10 volume % or more and 0.50 volume % or less,

[0059] The average grain size of the second hard phase is 0.03 μm or more and 0.50 μm or less.

[0060] The binding phase contains 80 mass % or more of cobalt,

[0061] The content of the binder phase in the cemented carbide is 8.0 volume % or more and 16.0 volume % or less,

[0062] The average particle size of the binder phase is 0.15 μm or more and 0.45 μm or less,

[0063] The 95% cumulative particle size D95 based on the area of ​​the bonding phase is 1.5 μm or less,

[0064] The dispersion degree of the binder phase is 0.15 or more and 0.25 or less.

[0065] The tool including the cemented carbide of the present disclosure can have a long tool life. The reason for this is presumably as follows.

[0066] (i) In the cemented carbide disclosed herein, the first hard phase is composed of tungsten carbide particles, the 10% cumulative particle size D10 of the first hard phase on an area basis is 0.30 μm or more and 0.60 μm or less, and the 90% cumulative particle size D90 of the first hard phase on an area basis is 0.90 μm or more and 1.40 μm or less. As a result, the cemented carbide has an excellent balance between mechanical strength and hardness, and can have excellent defect resistance and wear resistance at the same time.

[0067] (ii) In the cemented carbide disclosed herein, the second hard phase includes at least one first compound selected from the group consisting of TiNbC, TiNbN and TiNbCN, the content of the second hard phase of the cemented carbide is 0.10 volume % or more and 0.50 volume % or less, and the average particle size of the second hard phase is 0.03 μm or more and 0.50 μm or less. As a result, the second hard phase can finely divide the bonding phase, and the cemented carbide can have excellent resistance to welding. In addition, it is not easy to cause abnormal reduction in mechanical strength of the cemented carbide structure due to the formation of a condensate of the second hard phase or the presence of a coarse second hard phase, and the cemented carbide can have excellent resistance to defect.

[0068] (iii) In the cemented carbide disclosed in the present invention, the binding phase contains more than 80% by mass of cobalt, and the content of the binding phase of the cemented carbide is more than 8.0% by volume and less than 16.0% by volume. As a result, the mechanical strength of the cemented carbide is excellent, and it can have excellent defect resistance, and the welding resistance is also good. In the cemented carbide disclosed in the present invention, the average particle size of the binding phase is more than 0.15μm and less than 0.45μm, the 95% cumulative particle size D95 in the area basis of the binding phase is less than 1.5μm, and the dispersion of the binding phase is more than 0.15 and less than 0.25. As a result, the binding phase is finely dispersed in the cemented carbide, and the cemented carbide can have excellent welding resistance.

[0069] <Composition of cemented carbide>

[0070] The cemented carbide of the first embodiment is composed of a first hard phase, a second hard phase, and a binding phase. The cemented carbide of the first embodiment can also contain impurities as long as it does not damage the effect of the present disclosure. That is, the cemented carbide can be composed of a first hard phase, a second hard phase, a binding phase, and impurities. As impurities, for example, iron (Fe), molybdenum (Mo), calcium (Ca), silicon (Si), and sulfur (S) can be cited. The content of impurities in the cemented carbide (when there are two or more impurities, it is the total of their contents) is preferably 0 mass% or more and less than 0.1 mass%. The content of impurities in the cemented carbide is measured by ICP emission analysis (Inductively Coupled Plasma Emission Spectroscopy (measurement device: Shimadzu Corporation "ICPS-8100" (trademark)).

[0071] In the first embodiment, when the cemented carbide as a whole is 100% by volume, the content of the first hard phase of the cemented carbide can be set to a value obtained by subtracting the content of the second hard phase and the content of the bonding phase from 100% by volume. The content of the second hard phase of the cemented carbide and the content of the bonding phase of the cemented carbide are described later. The content of the first hard phase of the cemented carbide can also be, for example, 83.5% by volume or more and 91.9% by volume or less.

[0072] In the first embodiment, the content of the second hard phase of the cemented carbide is more than 0.10 volume % and less than 0.50 volume %. Thus, the resistance to welding of the cemented carbide is easily improved. If the content of the second hard phase is less than 0.10 volume %, the amount of the second hard phase present is small, the effect of dividing the binding phase is small, and the fine dispersion of the binding phase cannot be improved. If the content of the second hard phase exceeds 0.50 volume %, it becomes the cause of abnormal structures such as agglomerates of the second hard phase, and good fine dispersion and mechanical strength of the binding phase cannot be achieved. The lower limit of the content of the second hard phase of the cemented carbide can be more than 0.15 volume %, can be more than 0.20 volume %, or can be more than 0.30 volume %. The upper limit of the content of the second hard phase of the cemented carbide can be less than 0.45 volume %, or can be less than 0.40 volume %. The content of the second hard phase in the cemented carbide may be 0.15% by volume or more and 0.45% by volume or less, or 0.20% by volume or more and 0.40% by volume or less.

[0073] In embodiment one, the content of the bonding phase of cemented carbide is more than 8.0 volume % and less than 16.0 volume %. Thus, the strength of cemented carbide is easily improved. If the content of the bonding phase is less than 8.0 volume %, the mechanical strength is low and defects are easily generated. If it exceeds 16.0 volume %, the bonding phase volume becomes larger and the resistance to welding is reduced. The lower limit of the content of the bonding phase of cemented carbide can be more than 10.0 volume %, can be more than 12.0 volume %, or can be more than 13.0 volume %. The upper limit of the content of the bonding phase of cemented carbide can also be less than 14.0 volume %. The content of the bonding phase of cemented carbide can be more than 10.0 volume % and less than 16.0 volume %, or can be more than 12.0 volume % and less than 14.0 volume %.

[0074] The content rate of the first hard phase, the content rate of the second hard phase, and the content rate of the binder phase of the cemented carbide are measured in the following manner.

[0075] (A1) any surface or any cross section of the cemented carbide is subjected to mirror finishing. As the method of mirror finishing, for example, a method of grinding with diamond paste, a method of using a converged ion beam device (FIB device), a method of using a cross-section polisher device (CP device), and a method of combining them, etc. can be cited.

[0076] (B1) A reflected electron image is obtained by photographing the processed surface of cemented carbide using a scanning electron microscope ("JSM-7800F" manufactured by JEOL Ltd.). Five reflected electron images are prepared. The shooting areas of the five reflected electron images are different. The shooting position can be set arbitrarily. The conditions are set to an observation magnification of 3000 times, an accelerating voltage of 5 kV, and a reflected electron image. The shooting area of ​​the reflected electron image is set to the central part of the cross section of the cemented carbide, that is, the position of the part where the properties are obviously different from the main part, such as the vicinity of the surface of the cemented carbide, is not included (the shooting area is the position of the main part of the cemented carbide).

[0077] An example of a reflected electron image of a cemented carbide according to the first embodiment is shown in FIG. Figure 1 Indicates. Figure 1 In the figure, the white area corresponds to the first hard phase, the gray area corresponds to the bonding phase, and the black area corresponds to the second hard phase.

[0078] (C1) The imaging area of ​​(B1) is subjected to elemental analysis using an energy dispersive X-ray analyzer (SEM-EDX) attached to a SEM to obtain an elemental mapping image.

[0079] (D1) The reflected electron image obtained in the above (B1) is acquired by a computer and binarized using image analysis software (ImageJ ver.1.51J8). The binarization process uses two different thresholds to perform a first binarization process and a second binarization process.

[0080] The first binarization process is performed by making the computer acquire the reflected electron image and extracting only the second hard phase from the first hard phase, the second hard phase and the bonding phase in the reflected electron image. In the image after the first binarization process, the second hard phase is represented by black, and the first hard phase and the bonding phase are represented by white.

[0081] The second binarization process is performed as follows: a computer is caused to newly acquire a reflected electron image identical to the reflected electron image used in the first binarization process, and the second hard phase and the bonding phase in the reflected electron image are extracted. In the image after the second binarization process, the second hard phase and the bonding phase are represented in black, and the first hard phase is represented in white. The threshold value of binarization varies according to the contrast, and is therefore set for each image.

[0082] (E1) The element mapping image obtained by the above (C1) is overlapped with the first binarized image and the second binarized image obtained by the above (D1), thereby obtaining a first image in which the respective existence regions of the first hard phase, the second hard phase and the bonding phase are determined. In the first image, the region represented by white in the image after the second binarization process and in which tungsten (W) and carbon (C) exist in the element mapping image corresponds to the existence region of the first hard phase. In the first image, the region represented by white in the image after the first binarization process and by black in the image after the second binarization process and in which cobalt exists in the element mapping image corresponds to the existence region of the bonding phase. In the first image, the region represented by black in the image after the first binarization process and other than the existence region of the first hard phase and the existence region of the bonding phase determined above corresponds to the existence region of the second hard phase.

[0083] (F1) A rectangular measurement field of 40.3 μm in length and 30.2 μm in width is set in each of the five first images. Using the above-mentioned image analysis software, the area percentages of the first hard phase, the second hard phase, and the binder phase are measured with the area of ​​the entire measurement field as the denominator.

[0084] (G1) In the present disclosure, the average of the area percentages of the first hard phase in five measurement fields of view is equivalent to the content (volume %) of the first hard phase in the cemented carbide, the average of the area percentages of the second hard phase in five measurement fields of view is equivalent to the content (volume %) of the second hard phase in the cemented carbide, and the average of the area percentages of the bonding phase in five measurement fields of view is equivalent to the content (volume %) of the bonding phase in the cemented carbide.

[0085] Within the range measured by the applicant, it was confirmed that: as long as the measurement is performed on the same sample, even if the cutting position of the cemented carbide cross section is arbitrarily set, the shooting area described in (B1) above is arbitrarily set on the cross section, and the five measurement fields of view described in (F1) above are arbitrarily set, and the above steps are followed, the content of the first hard phase, the content of the second hard phase, and the content of the bonding phase of the cemented carbide are measured multiple times, there is almost no deviation in the measurement results.

[0086] <First hard phase>

[0087] "composition"

[0088] In the first embodiment, the first hard phase is composed of tungsten carbide particles (hereinafter also referred to as "WC particles".) Tungsten carbide particles (hereinafter also referred to as "WC particles".) are particles composed of tungsten carbide. As long as the effect of the present disclosure is not impaired, the first hard phase can contain iron (Fe), molybdenum (Mo), calcium (Ca), silicon (Si), sulfur (S), etc. in the WC particles or together with the WC particles. The content of iron (Fe), molybdenum (Mo), calcium (Ca), silicon (Si), and sulfur (S) in the first hard phase (in the case of two or more, the total of their content) is preferably 0 mass% or more and less than 0.1 mass%. The content of iron (Fe), molybdenum (Mo), calcium (Ca), silicon (Si), and sulfur (S) in the first hard phase is determined by ICP emission analysis.

[0089] D10 and D90

[0090] In the first embodiment, the 10% cumulative particle size D10 (hereinafter also referred to as "the D10 of the first hard phase") on an area basis of the first hard phase is greater than 0.30 μm and less than 0.60 μm, and the 90% cumulative particle size D90 (hereinafter also referred to as "the D90 of the first hard phase") on an area basis of the first hard phase is greater than 0.90 μm and less than 1.40 μm. Thus, the cemented carbide can have a high hardness, and a tool containing the cemented carbide can have excellent wear resistance. In addition, the tool can have excellent breakage resistance. When D10 and D90 of the first hard phase are respectively less than the aforementioned lower limit, the mechanical strength is low and defects are easily generated. When D10 and D90 of the first hard phase exceed the aforementioned upper limit, the hardness is low and the wear resistance is reduced.

[0091] The lower limit of D10 of the first hard phase may be 0.33 μm or more, 0.36 μm or more, 0.38 μm or more, or 0.40 μm or more. The upper limit of D10 of the first hard phase may be 0.55 μm or less, 0.53 μm or less, 0.50 μm or less, or 0.45 μm or less. D10 of the first hard phase may be 0.33 μm or more and 0.55 μm or more and 03.6 μm or more and 0.53 μm or less.

[0092] The lower limit of D90 of the first hard phase may be 0.95 μm or more, 1.00 μm or more, 1.05 μm or more, or 1.10 μm or more. The upper limit of D90 of the first hard phase may be 1.30 μm or less, 1.25 μm or less, or 1.24 μm or less. D90 of the first hard phase may be 0.95 μm or more and 1.30 μm or more and 1.00 μm or more and 1.25 μm or less.

[0093] In embodiment one, the lower limit of the average particle size of the first hard phase may be greater than 0.60 μm, or greater than 0.70 μm. The upper limit of the average particle size of the first hard phase may be less than 0.90 μm, or less than 0.80 μm. The average particle size of the first hard phase may be greater than 0.60 μm and less than 0.90 μm, or greater than 0.70 μm and less than 0.80 μm. In the present disclosure, the average particle size of the first hard phase refers to the arithmetic mean of the equal-area equivalent circle diameter (Heywood diameter, hereinafter also referred to as "equivalent circle diameter") of the first hard phase measured by the following measurement method.

[0094] In the present disclosure, the method for measuring D10, D90 and the average grain size of the first hard phase is as follows.

[0095] (A2) The region where the first hard phase exists is determined on the first image by the same method as (A1) to (E1) of the above-mentioned method for measuring the content of the first hard phase, the content of the second hard phase, and the content of the binder phase in the cemented carbide.

[0096] (B2) A rectangular measurement field of 40.3 μm in length and 30.2 μm in width was set in each of the five first images. The outer edge of each first hard phase in the measurement field was determined using image analysis software (ImageJ ver. 1.51J8), and the equivalent circle diameter of each first hard phase was calculated.

[0097] (C2) Based on the equivalent circle diameters of all the first hard phases in five measurement fields, D10, D90, and the average grain size of the first hard phase are calculated.

[0098] Within the range measured by the applicant, it was confirmed that as long as the measurement is performed on the same sample, even if the cutting position of the cross section of the cemented carbide is arbitrarily set, the shooting area described in (B1) above is arbitrarily set on the cross section, and the measurement field of view described in (B2) above is arbitrarily set, and the above steps are followed, the D10, D90 and average particle size of the first hard phase are measured multiple times, there is almost no deviation in the measurement results.

[0099] <Second hard phase>

[0100] "composition"

[0101] In the first embodiment, the second hard phase includes at least one first compound selected from the group consisting of TiNbC, TiNbN, and TiNbCN. This improves the welding resistance of the cemented carbide.

[0102] In the range that does not impair the effect of the present disclosure, the second hard phase is allowed to contain metal elements such as Ti compounds (TiCN, TiWC, etc.) not containing Nb, tungsten (W), chromium (Cr), and cobalt (Co) on the basis of the first compound. The total content of W, Cr, and Co in the second hard phase may be, for example, 0 mass% or more and 3 mass% or less. The content of W, Cr, and Co in the second hard phase is measured by TEM-DEX.

[0103] That the second hard phase includes at least one first compound selected from the group consisting of TiNbC, TiNbN, and TiNbCN was confirmed by the following procedure.

[0104] (A3) Use an ion microtome (device: IB09060CIS (trademark) manufactured by JEOL Ltd.) to slice any position of the cemented carbide to prepare a sample with a thickness of 30 to 100 nm. The acceleration voltage of the ion microtome is 6 kV for the thinning process and 2 kV for the finishing process.

[0105] (B3) The sample was observed at 50,000 times using a scanning transmission electron microscope (STEM) (device: JFM-ARM300F (trademark) manufactured by JEOL Ltd.) to obtain a STEM-HAADF (high-angle annular dark fields scanning transmission electron microscope) image. The shooting area of ​​the STEM-HAADF image was set to the central part of the sample, that is, the position of the part where the properties are obviously different from the main part, such as the surface of the cemented carbide, was not included (the shooting area is the position of the main part of the cemented carbide). The measurement condition is an acceleration voltage of 200 kV.

[0106] (C3) Next, spot analysis is performed on the second hard phase particles present in the STEM-HAADF image using EDX attached to the STEM to quantify the elements constituting the second hard phase particles. In the STEM-HAADF image, the second hard phase particles are identified as black particles. For each second hard phase, the spot size is set within a range that includes only the second hard phase. As a result of quantifying the constituent elements, it is confirmed that in the presence of titanium (Ti) and niobium (Nb), and one or both of carbon (C) and nitrogen (N), the second hard phase contains at least one first compound selected from the group consisting of TiNbC, TiNbN, and TiNbCN.

[0107] 《Average particle size》

[0108] In the first embodiment, the average particle size of the second hard phase is greater than 0.03 μm and less than 0.50 μm. As a result, the welding resistance of the cemented carbide is improved. In addition, the second hard phase is not easy to become the starting point of destruction, and the defect resistance of the tool containing the cemented carbide is improved. If the average particle size of the second hard phase is less than 0.03 μm, the welding resistance of the cemented carbide is easily reduced. If the average particle size of the second hard phase exceeds 0.50 μm, the defect resistance of the cemented carbide is easily reduced. The lower limit of the average particle size of the second hard phase can be greater than 0.03 μm, can be greater than 0.04 μm, can be greater than 0.05 μm, can be greater than 0.06 μm, can be greater than 0.15 μm, or can be greater than 0.20 μm. The upper limit of the average particle size of the second hard phase can be less than 0.50 μm, can be less than 0.45 μm, can be less than 0.40 μm, or can be less than 0.35 μm. The average grain size of the second hard phase may be 0.04 μm or more and 0.45 μm or less, or 0.05 μm or more and 0.40 μm or less.

[0109] The method for measuring the average grain size of the second hard phase is as follows.

[0110] (A4) The region where the second hard phase exists is determined on the first image by the same method as (A1) to (E1) of the above-mentioned method for measuring the content of the first hard phase, the content of the second hard phase, and the content of the binder phase in the cemented carbide.

[0111] (B4) A rectangular measurement field of 40.3 μm in length and 30.2 μm in width was set in each of the five first images. The outer edge of each second hard phase in the measurement field was determined using image analysis software (ImageJ ver. 1.51J8), and the equivalent circle diameter of each second hard phase was calculated.

[0112] (C4) Calculate the average grain size of the second hard phase based on the equivalent circle diameters of all the second hard phases in five measurement fields. In the present disclosure, the average grain size of the second hard phase refers to the arithmetic average of the equivalent circle diameters (Heywood diameters) of multiple grains constituting the second hard phase.

[0113] Within the range measured by the applicant, it was confirmed that as long as the measurement was performed on the same sample, even if the cutting position of the cross section of the cemented carbide was arbitrarily set, the shooting area described in (B1) above was arbitrarily set on the cross section, and the measurement field of view described in (B4) above was arbitrarily set, and the average particle size of the second hard phase was measured multiple times following the above steps, there was almost no deviation in the measurement results.

[0114] <Joint phase>

[0115] "composition"

[0116] In the first embodiment, the binding phase contains 80% or more of cobalt. The content of cobalt in the binding phase may be 90% or more and 100% or less, 95% or more and 100% or less, 98% or more and 100% or less, or 100% or less. The content of cobalt in the binding phase is determined by ICP emission analysis.

[0117] The bonding phase may include iron (Fe), nickel (Ni), tungsten (W), chromium (Cr), vanadium (V), titanium (Ti), niobium (Nb), tantalum (Ta), etc., in addition to the first element.

[0118] 《Average particle size and D95》

[0119] In the first embodiment, the average particle size of the bonding phase is greater than 0.15 μm and less than 0.45 μm, the 95% cumulative particle size D95 (hereinafter also referred to as "D95 of the bonding phase") in the area basis of the bonding phase is less than 1.5 μm, and the dispersion of the bonding phase is greater than 0.15 and less than 0.25. As a result, the cemented carbide can have excellent resistance to welding. In order to make the average particle size of the bonding phase less than 0.15 μm, it is mainly necessary to refine the particle size of the first hard phase, in which case the mechanical strength is reduced. When the average particle size of the bonding phase exceeds 0.45 μm, the resistance to welding is reduced. When the D95 of the bonding phase exceeds 1.5 μm, local welding occurs and defects are easily generated.

[0120] The lower limit of the average particle size of the binding phase is greater than 0.15 μm, and can be greater than 0.20 μm, or greater than 0.30 μm. The upper limit of the average particle size of the binding phase is less than 0.45 μm, or less than 0.40 μm. The average particle size of the binding phase can be greater than 0.15 μm and less than 0.40 μm, can be greater than 0.20 μm and less than 0.45 μm, or can be greater than 0.30 μm and less than 0.40 μm. In the present disclosure, the average particle size of the binding phase refers to the arithmetic mean of the equal-area equivalent circle diameter (Heywood diameter) of the binding phase measured by the following measurement method.

[0121] The lower limit of D95 of the binding phase may be 0.30 μm or more, 0.40 μm or more, 0.45 μm or more, 0.60 μm or more, 0.65 μm or more, or 0.80 μm or more. The upper limit of D95 of the binding phase is 1.50 μm or less, 1.30 μm or less, 1.20 μm or less, or 1.00 μm or less. D95 of the binding phase may be 0.30 μm or more and 1.50 μm or more and 0.60 μm or more and 1.30 μm or less.

[0122] The average particle size and D95 ​​of the binding phase are measured as follows.

[0123] (A5) The region where the binder phase exists is determined on the first image by the same method as (A1) to (E1) of the above-mentioned method for measuring the content of the first hard phase, the content of the second hard phase, and the content of the binder phase in the cemented carbide.

[0124] (B5) A rectangular measurement field of 40.3 μm in length and 30.2 μm in width was set in each of the five first images. The outer edge of each binding phase in the measurement field was determined using image analysis software (ImageJ ver. 1.51J8), and the equivalent circle diameter of each binding phase was calculated.

[0125] (C5) Calculate the average particle size and D95 ​​of the binder phase based on the equivalent circle diameters of all binder phases in five measurement fields. In the present disclosure, the average particle size of the binder phase refers to the arithmetic mean of the equivalent circle diameters (Heywood diameters) of multiple grains constituting the binder phase.

[0126] Within the range measured by the applicant, it was confirmed that as long as the measurement is performed on the same sample, even if the cutting position of the cemented carbide cross section is arbitrarily set, the shooting area described in (B1) above is arbitrarily set on the cross section, and the measurement field of view described in (C5) above is arbitrarily set, and the above steps are followed, the average particle size of the binding phase and D95 ​​are measured multiple times, there is almost no deviation in the measurement results.

[0127] Dispersion

[0128] In the first embodiment, the dispersion of the bonding phase is greater than 0.15 and less than 0.25. As a result, the bonding phase is finely dispersed, the cemented carbide structure becomes homogeneous, and the cemented carbide can have excellent resistance to welding. In order to make the dispersion of the bonding phase less than 0.15, it is mainly necessary to refine the particle size of the first hard phase, in which case the mechanical strength is reduced. If the dispersion of the bonding phase exceeds 0.25, the resistance to welding is reduced. The lower limit of the dispersion of the resistant welding bonding phase is greater than 0.15, and can be greater than 0.16, or greater than 0.17. The upper limit of the dispersion of the bonding phase is less than 0.25, and can be less than 0.24, can be less than 0.23, or can be less than 0.21. The dispersion of the bonding phase can be greater than 0.16 and less than 0.24, or can be greater than 0.17 and less than 0.23.

[0129] In the present disclosure, the dispersion of the binding phase is measured using a Voronoi diagram. The specific measurement method is as follows.

[0130] (A6) The region where the binder phase exists is determined on the first image by the same method as (A1) to (E1) of the above-mentioned method for measuring the content of the first hard phase of cemented carbide, the content of the binder phase, and the content of the binder phase.

[0131] (B6) A rectangular measurement area of ​​40.3 μm × 30.2 μm is set in the first image. In this measurement area, the image analysis software (ImageJ ver.1.51J8) is used to calculate the Voronoi region with the centroid position of each bond phase as the mother point, and a Voronoi diagram is produced. The Voronoi region refers to the area surrounded by the Voronoi boundary formed by dividing two adjacent mother points by a perpendicular bisector when multiple mother points are arranged on the same plane.

[0132] Will be based on Figure 1 The Voronoi diagram made from the reflected electron image shown is Figure 2 .exist Figure 2 In the figure, the regions enclosed by white lines are Voronoi regions.

[0133] (C6) Using image analysis software (ImageJ ver.1.51J8), the Voronoi area (μm 2 ). Here, the Voronoi area in the measurement area refers to the Voronoi area in which the entire Voronoi area exists in the measurement area. Therefore, when a part of the Voronoi area exists outside the measurement area, the Voronoi area is not included in the Voronoi area in the measurement area. The standard deviation σ of all the Voronoi areas in the measurement area is calculated.

[0134] (D6) The calculation of the above-mentioned standard deviation σ is performed in five different measurement areas that do not overlap with each other. In the present disclosure, the average of the standard deviations σ in the five measurement areas corresponds to the dispersion of the binder phase of the cemented carbide.

[0135] Within the range measured by the applicant, it was confirmed that as long as the measurement was performed on the same sample, even if the cutting position of the cross section of the cemented carbide was arbitrarily set, the measurement area described in (B6) was arbitrarily set, and the above steps were followed to perform the dispersion measurement of the bonding phase multiple times, there was almost no deviation in the measurement results.

[0136] <Nb / (Ti+Nb) percentage in cemented carbide>

[0137] In the cemented carbide of the first embodiment, the mass-based percentage of niobium relative to the total of titanium and niobium (hereinafter, also referred to as "Nb / (Ti+Nb) percentage") can be greater than 2% and less than 30%, or greater than 3% and less than 20%. As a result, the second hard phase can be finely dispersed in the cemented carbide, and the welding resistance of the cemented carbide can be improved. In the case where the Nb / (Ti+Nb) percentage is less than 2% or does not exist, the dispersion effect of the second hard phase particles is small, and the welding resistance is easily reduced. In the case where the Nb / (Ti+Nb) percentage exceeds 30%, the second hard phase particles become prone to grain growth, the mechanical strength is reduced, and defects are easily generated. The lower limit of the Nb / (Ti+Nb) percentage can be greater than 4%, can be greater than 5%, or can be greater than 10%. The upper limit of the Nb / (Ti+Nb) percentage can be less than 18%, or can be less than 16%. The Nb / (Ti+Nb) percentage may be 4% to 18% inclusive, or 5% to 16% inclusive.

[0138] In the present disclosure, the mass-based percentage of niobium relative to the total of titanium and niobium in cemented carbide is measured by ICP emission spectrometry.

[0139] In the range measured by the applicant, it was confirmed that even if the average measurement of the Nb percentage in cemented carbide was performed multiple times for a plurality of samples manufactured under the same conditions, there was almost no variation in the measurement results.

[0140] <Vanadium content in cemented carbide>

[0141] The vanadium content of the cemented carbide of the first embodiment can be 0 mass % or more and 0.2 mass % or less, or 0 mass % or more and 0.1 mass % or less. Thus, it is possible to suppress the formation of coarse precipitates containing vanadium in the cemented carbide and the precipitation of vanadium at the interface between WC particles. Thus, the reduction of the mechanical properties of the cemented carbide is suppressed. The vanadium content of the cemented carbide is measured by ICP emission analysis.

[0142] <Chromium content of cemented carbide>

[0143] The chromium content of the cemented carbide of the first embodiment can be 0.2 mass % or more and 1.0 mass % or less, or 0.4 mass % or more and 0.8 mass % or less. Thus, it is possible to suppress the formation of coarse precipitates containing chromium in the cemented carbide and the precipitation of chromium at the interface between WC particles. Thus, the reduction of the mechanical properties of the cemented carbide is suppressed. The chromium content of the cemented carbide is measured by ICP emission analysis.

[0144] <Manufacturing method>

[0145] The cemented carbide according to the first embodiment can be produced, for example, by the following method.

[0146] 《Preparation of raw materials》

[0147] Prepare raw material powders. As the raw material of the first hard phase, prepare two types of tungsten carbide (WC) powders with different average particle sizes. Hereinafter, the two WC powders are also referred to as the first WC powder and the second WC powder. As the raw material powder of the second hard phase, prepare carbides, nitrides, carbonitrides, oxides, composite carbonitrides, etc. containing one or both of titanium and niobium. Examples of the raw material of the second hard phase include titanium carbonitride (TiCN) powder and niobium carbide (NbC) powder. As the raw material of the binding phase, prepare cobalt (Co) powder, and as needed, prepare iron (Fe) powder and nickel (Ni) powder. Prepare chromium carbide (Cr) powder as a grain growth inhibitor. 3 C 2 ) powder, vanadium carbide (VC) powder.

[0148] The average particle size of the first WC powder can be set to 0.3 μm or more and 0.8 μm or less. The average particle size of the second WC powder can be set to 0.1 or more and 0.5 μm or less. The average particle size of the first WC powder is larger than the average particle size of the second WC powder. The average particle size is measured using a particle size distribution measuring device manufactured by Microtrac (trade name: MT3300EX).

[0149] The average particle size of titanium carbonitride (TiCN) powder can be set to be greater than 0.1 μm and less than 1.0 μm. The average particle size of niobium carbide (NbC) powder can be set to be greater than 0.1 μm and less than 2.0 μm. The average particle size of cobalt (Co) powder can be set to be greater than 0.1 μm and less than 5 μm. The average particle size of iron (Fe) powder can be set to be greater than 0.1 μm and less than 5 μm. The average particle size of nickel (Ni) powder can be set to be greater than 0.1 μm and less than 5 μm. The average particle size of these raw material powders refers to the median diameter d50 based on the number of spherical equivalent diameters of the raw material powders. The average particle size of the raw material powder is measured using a particle size distribution measuring device manufactured by Microtrac (trade name: MT3300EX).

[0150] 《Mixing of raw material powders》

[0151] Next, the raw material powders are mixed to obtain a mixed powder. As a mixing device, a ball mill, a grinding mill, a Karman mixer, etc. can be used. The mixing time can be appropriately adjusted according to each mixing method. First, by putting the raw material powder of the second hard phase (for example, titanium carbonitride (TiCN) powder, niobium carbide (NbC) powder) into a mixing device and pre-mixing it for a predetermined time, these powders can also be miniaturized. The pre-mixing time can be appropriately set according to the average particle size of the raw material powder of the second hard phase. For example, when the average particle size of the titanium carbonitride (TiCN) powder is greater than 0.1μm and less than 1.0μm, and the average particle size of the niobium carbide (NbC) powder is greater than 0.1μm and less than 2.0μm, the pre-mixing time can be set to more than 60 minutes and less than 120 minutes. Afterwards, the raw material powder of the binding phase containing the first WC powder, the second WC powder, the grain growth inhibitor, and the cobalt powder is put into the mixing device and mixed with other raw material powders to obtain a mixed powder.

[0152] The mixing ratio of the raw material powders is adjusted so that, in the cemented carbide, the content of the second hard phase is 0.10 volume % or more and 0.50 volume % or less, and the content of the binder phase is 8.0 volume % or more and 16.0 volume % or less.

[0153] When vanadium carbide (VC) powder is used as a particle growth inhibitor, the vanadium content in the mixed powder is adjusted to be 0.2 mass % or less. 3 C 2 ) powder as a particle growth inhibitor, the Cr content in the mixed powder is adjusted to 3 C 2 The content of is 1.3 mass % or less.

[0154] Taking Shape

[0155] Next, the mixed powder is molded into a desired shape to obtain a molded body. The molding method and molding conditions may be general methods and conditions, and are not particularly limited.

[0156] "sintering"

[0157] Next, the compact is placed in a sintering furnace and sintered at 1380-1420°C and 0.3-30 kPa for 0-120 minutes in a vacuum atmosphere or a gas atmosphere such as nitrogen or argon to obtain a sintered body. Next, the sintered body can be rapidly cooled to room temperature to obtain a cemented carbide.

[0158] 《Characteristics of the manufacturing method》

[0159] In the above-mentioned mixing step, the first WC powder and the second WC powder having different average particle sizes are mixed. It is speculated that the first WC particles constituting the first WC powder and the second WC particles constituting the second WC powder are mixed in the structure of the cemented carbide and the ultrafine second WC particles are buried in the gaps between the fine first WC particles, thereby reducing the mean free path of the binding phase. It is speculated that, as a result, the binding phase is easily finely dispersed in the cemented carbide.

[0160] In the mixing step, raw material powders of the second hard phase (e.g., titanium carbonitride (TiCN) powder, niobium carbide (NbC) powder) are put into a mixing device and pre-mixed for a predetermined time, thereby controlling the powders to a predetermined particle size. It is presumed that, as a result, the binder phase is easily finely dispersed in the cemented carbide.

[0161] In the past, in order to finely disperse the binding phase containing cobalt in cemented carbide, it was necessary to sinter at a temperature exceeding 1420°C. However, if sintering is performed at a temperature exceeding 1420°C, the WC particles are prone to grain growth, and the binding phase also coarsens with the grain growth of the WC particles. In order to refine the binding phase, it is necessary to add a large amount of vanadium and chromium that have a grain growth inhibition effect, or to sinter at a temperature below 1420°C. If a large amount of vanadium and chromium that have a grain growth inhibition effect is added, coarse precipitates are formed in the cemented carbide or vanadium and chromium are precipitated at the interface between the WC particles, thereby reducing the mechanical properties of the cemented carbide. If sintering is performed at a temperature below 1420°C, the binding phase containing cobalt is not finely dispersed in the cemented carbide. In the previous method for manufacturing cemented carbide, good fine dispersibility of the binding phase and good mechanical strength of the cemented carbide can be achieved at the same time.

[0162] In the production method disclosed in the present invention, when vanadium carbide (VC) powder is used as a particle growth inhibitor, the vanadium content in the mixed powder is adjusted to be 0.2 mass % or less, and when chromium carbide (Cr 3 C2 ) powder, the Cr content in the mixed powder is adjusted to 3 C 2 The content is made less than 1.3% by mass. Furthermore, the content of the cobalt powder in the mixed powder is adjusted so that the content of the cemented carbide bonding phase is greater than 8.0% by volume and less than 16.0% by volume. As the raw powder of the second hard phase, a powder containing a predetermined amount of niobium is used. Thus, when sintered at a temperature below 1420°C, the grain growth of the WC particles is suppressed, and at the same time, niobium is dissolved in the bonding phase and re-precipitated together with titanium in a particularly coarse bonding phase portion of the bonding phase, thereby making it possible to finely divide the bonding phase and improve the fine dispersion of the bonding phase. The above-mentioned manufacturing method is what the inventors have discovered.

[0163] When niobium is not contained in the raw material powder of the second hard phase, the dispersibility of the second hard phase is reduced, and it is difficult to obtain the effect of dividing the binding phase. In addition, when the raw material powder of the second hard phase contains a large amount of niobium, the grain growth of the second hard phase is promoted and a coarse second hard phase is precipitated, which reduces the properties such as bending strength.

[0164] [Implementation method 2: Tools]

[0165] A tool according to one embodiment of the present disclosure (hereinafter, also referred to as "embodiment 2") is a cutting tool comprising the cemented carbide described in embodiment 1. The tool of embodiment 2 can have a long tool life. It is presumed that this is because the cemented carbide has excellent resistance to welding in addition to the excellent mechanical strength that the cemented carbide originally has. The tool of embodiment 2 preferably comprises the cemented carbide of embodiment 1 at least in the portion related to cutting. The portion related to cutting refers to an area with a distance of 500 μm or less from the blade tip.

[0166] As the above-mentioned tools, there can be listed drills, micro drills, end mills, tool tip exchangeable cutting inserts for drills, tool tip exchangeable inserts for end mills, throwaway inserts for milling, throwaway inserts for turning, metalworking saws, gear cutting tools, reamers, taps, cutting tools, wear-resistant tools, tools for friction stir welding, etc.

[0167] Example

[0168] The present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to these examples.

[0169] [Production of cemented carbide]

[0170] As raw material powders, a first tungsten carbide (WC) powder, a second tungsten carbide (WC) powder, and a chromium carbide (Cr 3 C 2) powder, vanadium carbide (VC) powder, titanium carbonitride (TiCN) powder, niobium carbide (NbC) powder, and cobalt (Co) powder.

[0171] The average particle diameters of the first tungsten carbide powder and the second tungsten carbide powder are shown in the columns “first WC powder” and “second WC powder” in Table 1.

[0172] Cr 3 C 2 The average particle size of the powder was 1.5 μm, the average particle size of the VC powder was 0.8 μm, the average particle size of the TiCN powder was 0.7 μm, the average particle size of the NbC powder was 1.0 μm, and the average particle size of the Co powder was 1.2 μm. The average particle size of the raw material powder was measured using a particle size distribution measuring device manufactured by Microtrac (trade name: MT3300EX).

[0173] The raw material powders were mixed in the ratios described in the "Raw Material Powder" column of Table 1 to obtain a mixed powder. A ball mill was used as a mixing device. First, TiCN powder and NbC powder were put into the mixing device and pre-mixed. The pre-mixing mixing time is shown in the "Pre-mixing Time" column of Table 2. When "-" is recorded in the "Pre-mixing Time" column, it means that the TiCN powder and NbC powder are mixed simultaneously with other raw material powders without pre-mixing the TiCN powder and NbC powder. After that, the raw material powder containing the first WC powder, the second WC powder, the grain growth inhibitor, and the binding phase of the Co powder was put into the mixing device and mixed. The mixing time (excluding the pre-mixing mixing time) is shown in the "Mixing Time" column of Table 2.

[0174] The mixed powder was pressed into a A round rod-shaped molded body.

[0175] The obtained compact was placed in a sintering furnace, and the temperature and pressure were raised to the temperature and pressure recorded in the "Temperature" and "Pressure" columns of the "Sintering Conditions" in Table 2, and the sintered compact was obtained for the time recorded in the "Time" column. Next, the sintered compact was rapidly cooled to room temperature to obtain the cemented carbide of each sample.

[0176] [Tool production]

[0177] The obtained cemented carbide round rod was processed to produce End mill.

[0178] Table 1

[0179]

[0180] Table 2

[0181]

[0182] [evaluate]

[0183] <Carbide>

[0184] 《Composition of Cemented Carbide》

[0185] For each sample of cemented carbide, the content (volume %) of the first hard phase, the second hard phase and the bonding phase was measured. The specific measurement method is described in the first embodiment. The results are shown in the "First Hard Phase Content", "Second Hard Phase Content", and "Bonding Phase Content" columns of "Cemented Carbide" in Table 3. "Second Hard Phase: 0.00, TiCN: 0.30" in the "Second Hard Phase Content" column of Sample 109 means that there is no second hard phase in Sample 109, and instead, there is 0.30 volume % TiCN.

[0186] 《D10, D90 and average particle size of the first hard phase》

[0187] For each sample of cemented carbide, the D10, D90 and average grain size of the first hard phase were measured. The specific measurement method is described in Embodiment 1. The results are shown in the "D10", "D90" and "Average Grain Size" columns of "First Hard Phase" in Table 4.

[0188] 《Composition of the second hard phase》

[0189] The composition of the second hard phase was determined for the cemented carbide of each sample. The specific measurement method is described in the first embodiment. In the area where the second hard phase exists in the STEM-HAADF image, in the area where titanium (Ti) and niobium (Nb) and one or both of carbon (C) and nitrogen (N) exist, it is confirmed that the second hard phase contains at least one first compound selected from the group consisting of TiNbC, TiNbN and TiNbCN. In the case where the first compound exists in the second hard phase, the "First Compound" column of the "Second Hard Phase" in Table 4 indicates "Present". In the case where the first compound does not exist in the second hard phase, the "First Compound" column of the "Second Hard Phase" in Table 4 indicates "None". The record of "-" in the "Composition" column indicates that the second hard phase does not exist.

[0190] 《Average particle size of the second hard phase》

[0191] The average grain size of the second hard phase was measured for each sample of cemented carbide. The specific measurement method is described in Embodiment 1. The results are shown in the "Average Grain Size" column of "Second Hard Phase" in Table 4.

[0192] Composition of the combined phase

[0193] The cobalt content of the binder phase was measured for each sample of cemented carbide by ICP emission analysis, and it was confirmed that the cobalt content of the binder phase was 80% by mass or more in all samples.

[0194] 《Average particle size of binding phase and D95》

[0195] The average grain size and D95 ​​of the binder phase were measured for each sample of cemented carbide. The specific measurement method is described in Embodiment 1. The results are shown in the "Average Grain Size" and "D95" columns of "Binder Phase" in Table 4.

[0196] 《Dispersion of the combined phase》

[0197] The dispersion of the binder phase was measured for each sample of cemented carbide. The specific measurement method is described in Embodiment 1. The results are shown in the "Dispersion" column of "Binding Phase" in Table 4.

[0198] 《Nb / (Ti+Nb) percentage in cemented carbide》

[0199] The mass percentage of niobium (Nb percentage) relative to the total of titanium and niobium in the cemented carbide of each sample was measured by ICP emission spectroscopy. The results are shown in the "Nb / (Ti+Nb) percentage" column of "Cemented Carbide" in Table 3.

[0200] 《Vanadium content and chromium content of cemented carbide》

[0201] The vanadium content and the chromium content of the cemented carbide of each sample were measured by ICP emission spectrometry. The results are shown in the "V content" and "Cr content" columns of "cemented carbide" in Table 3.

[0202] Table 3

[0203]

[0204] Table 4

[0205]

[0206] <Tools>

[0207] <Cutting test>

[0208] Using the end mill of each sample, a cutting test was performed under the following cutting conditions to evaluate the defect resistance and welding resistance. The defect resistance was evaluated based on the cutting length (m) at which the defect reached 100 μm. The longer the cutting length, the better the defect resistance and the longer the tool life. The welding resistance was evaluated based on the average welding width (μm) at the time of the defect. When the welding width is less than 30 μm, it means that the welding resistance is excellent. The obtained results (i.e., the cutting length and the welding width) are recorded in the "Defect Resistance [m]" and "Welding Resistance [μm]" items of Table 5.

[0209] (Cutting conditions)

[0210] Workpiece: Ti-6Al-4V (titanium alloy (titanium-based difficult-to-cut materials))

[0211] Cutting speed: 120m / min

[0212] Feed rate: 0.02mm / edge

[0213] Axial cutting depth: 2.0mm

[0214] Radial cutting depth: 2.5mm

[0215] Presence of water-soluble coolant: Yes

[0216] Table 5

[0217]

[0218] <Investigation>

[0219] The cemented carbides and tools of samples 1 to 14 correspond to the examples. The cemented carbides and tools of samples 101 to 110 correspond to the comparative examples. It was confirmed that the tool life of the tools of samples 1 to 14 was longer than that of the tools of samples 101 to 110. Furthermore, it was confirmed that the tools of samples 1 to 14 were excellent in welding resistance.

[0220] As mentioned above, although the embodiment and the example of this disclosure were described, it is originally planned that the configurations of each embodiment and the example described above are appropriately combined or modified in various ways.

[0221] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.

Claims

1. A cemented carbide, the cemented carbide being a cemented carbide composed of a first hard phase, a second hard phase, and a bonding phase, wherein: The first hard phase is composed of tungsten carbide particles, The 10% cumulative grain size D10 of the first hard phase on an area basis is 0.30 μm or more and 0.60 μm or less, The 90% cumulative grain size D90 of the first hard phase on an area basis is 0.90 μm or more and 1.40 μm or less, The second hard phase includes at least one first compound selected from the group consisting of TiNbC, TiNbN and TiNbCN, The content of the second hard phase in the cemented carbide is 0.10 volume % or more and 0.50 volume % or less, The average grain size of the second hard phase is 0.03 μm or more and 0.50 μm or less. The binding phase contains 80 mass % or more of cobalt, The content of the binder phase in the cemented carbide is 8.0 volume % or more and 16.0 volume % or less, The average particle size of the binder phase is 0.15 μm or more and 0.45 μm or less, The 95% cumulative particle size D95 based on the area of ​​the bonding phase is 1.5 μm or less, The dispersion degree of the binder phase is 0.15 or more and 0.25 or less.

2. The cemented carbide according to claim 1, wherein: In the cemented carbide, the mass-based percentage of niobium to the total of titanium and niobium is 3% or more and 20% or less.

3. The cemented carbide according to claim 1 or 2, wherein: The dispersion is the standard deviation of the area of ​​each Voronoi region in the Voronoi diagram obtained by performing Voronoi segmentation with the center of gravity of the second hard phase as the parent point. The Voronoi diagram is obtained by the following method: extracting the second hard phase from a reflected electron image obtained by photographing a cross section of the cemented carbide using a scanning electron microscope, setting a rectangular measurement field of 24.9 μm × 18.8 μm in the image after binarization of the reflected electron image, performing Voronoi segmentation with the center of gravity of the extracted second hard phase as a parent point in the measurement field, and calculating the Voronoi areas of all the parent points.

4. A tool comprising the cemented carbide according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Hard metal and manufacturing method therefor

    JP2009024214A

  • Cemented carbide

    JP2013060666A

  • Hard metal alloy

    JP2016098393A

  • WC-based hard metal-made cutting tool excellent in plastic deformation resistance and defect resistance, and surface-coated WC-based hard metal-made cutting tool

    JP2021134364A

  • Cutting insert and cutting tool

    WO2018180911A1